A case study of the improvement in batik production - Mohamad Adam, Hassan (2015)
The process improvement in producing batik is an important aspect for the development of Malaysian SMEs. The unwanted process in production of batik can affect the company’s image and also involved the customer dissatisfaction. The aim of this research is to identify the critical process in production of batik and at the same time some improvement plan can be recommended. The scope of this study is focusing on production line of batik such as the process flow, workstations involved, footsteps, resource capacity, cycle time and etc. A quantitative data are collected through the site visit of Batik RM Company. The results of this research show that company is facing a problem with total average time at each of the workstations. From the research that has been done, proves that kaizen activities and line balancing improve the productivity and process improvement. However, to achieve more successful and effective improvement, further work standardization on each process is needed. This study is conducted by using the time study and using Microsoft Excel software to solve it.